Fun meets knowledge: English enrichment through Camp America - Stella Prancisca (Journal of English Language Teaching Innovations and Materials (Jeltim), 2019)
American Corner (Amcor) of Tanjungpura University is aware of the need to provide its EFL learners with an English community which facilitate the learners with English speaking atmosphere namely Camp America. Through Camp America program, the participants obtain some crucial learning benefits such as the opportunity of English interactive fun activities in a variety of settings like singing, games, and seminars. Also friendly engaging conversations with native speakers and local fluent English speaking instructors or mentors. Camp America becomes a helpful alternative to tackle limited opportunities of EFL teachers in providing their students with English community and native speakers. Through which the participants can benefit from both recreational English learning and direct engagement with authentic English speaking space that provides participants both target language community and American culture as well as media of enhancing their integrated language skills that they can apply them into a real life practice.